COOL: A framework for conversational OLAP. Issue 104 (February 2022) - Francia, Matteo; Gallinucci, Enrico; Golfarelli, Matteo
Abstract: The democratization of data access and the adoption of OLAP in scenarios requiring hand-free interfaces push towards the creation of smart OLAP interfaces. In this paper, we introduce COOL, a framework devised for COnversational OLap applications. COOL interprets and translates a natural language dialog into an OLAP session that starts with a GPSJ (Generalized Projection, Selection, and Join) query and continues with the application of OLAP operators. The interpretation relies on a formal grammar and on a repository storing metadata and values from a multidimensional cube. In case of ambiguous or incomplete text description, COOL can obtain the correct query either through automatic inference or user interactions to disambiguate the text. Our tests show very promising results in terms of effectiveness, efficiency, and user experience. Besides adding novel support to the interpretation and translation of complete analytical OLAP sessions, COOL achieves an average accuracy of 94% in the interpretation of GPSJ queries from real datasets. Highlights: COOL interprets and translates a natural language dialog into an OLAP query. COOL handles both full queries and OLAP operators. The interpretation relies on a formal grammar and on a knowledge base storing metadata. Ambiguities are solved either through automatic inference or through interactions with the user. COOL achieves state-of-the-art accuracy in the interpretation of GPSJ queries.